Comparison between laboratorial and field bituminous mixtures - Pereira, Paulo A. A. (1997)
This paper presents the results of a study where the fatigue life of three mixes was evaluated and compared. The mixes were all produced with the exact same materials. However, the preparation process differed. One was mixed and compacted in laboratory, the other was mixed in plant and compacted in laboratory and the third was mixed and compacted in the field. The mixes were compacted in the laboratory using the rolling wheel compactor. The field compaction was achieved by tire and steel rollers. The fatigue life of the mixes was compared based on the results of the four point bending beam test executed at 10 and 25°C. Furthermore comparisons were made between fatigue life predicted by the Shell, Brown, The Asphalt Institute, SHRP-A003A program procedures and the laboratory test results.